2017
DOI: 10.1016/j.bjorl.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus and students in Brazil: an assessment of knowledge of a common infection – preliminary report

Abstract: Knowledge of HPV by the population evaluated in this study is partial and fragmented. Lack of knowledge may contribute to the further spread of the disease. Public health policies for education and guidance of the population should be implemented in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
0
7
0
12
Order By: Relevance
“…Changes were implemented in the 2016 vaccination calendar, and the 2 nd dose was no longer necessary, given that studies showed that the antibody response was not different for girls who had received the 1 st , the 2 nd , and the 3 rd doses when compared with those who had received only the 1 st and the last doses, so the 2 nd phase began focusing on the age (between 9 and 13 years old) and on the number of doses (the 1 st and the last, 6 months later). The vaccine is safe, effective, and the main way to prevent the 4 types of HPV (6,11,16,18), being the viruses type 16 and type 18 present in 70% of the UCC cases, and types 6 and 11 present in 90% of the cases of genital warts. This year, the 2018 campaign wants to elicit the importance of the carers in what comes to the future and education of the girls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes were implemented in the 2016 vaccination calendar, and the 2 nd dose was no longer necessary, given that studies showed that the antibody response was not different for girls who had received the 1 st , the 2 nd , and the 3 rd doses when compared with those who had received only the 1 st and the last doses, so the 2 nd phase began focusing on the age (between 9 and 13 years old) and on the number of doses (the 1 st and the last, 6 months later). The vaccine is safe, effective, and the main way to prevent the 4 types of HPV (6,11,16,18), being the viruses type 16 and type 18 present in 70% of the UCC cases, and types 6 and 11 present in 90% of the cases of genital warts. This year, the 2018 campaign wants to elicit the importance of the carers in what comes to the future and education of the girls.…”
Section: Discussionmentioning
confidence: 99%
“…A study with Brazilian university students showed that 77% heard about HPV, 65% from the media, 38% from television, 28% from health professionals and 31% from the vaccine. 18 This study presents the strategies used by the nurses in a health center to inform women regarding HPV. They make use of rounds of conversations and educative groups to encourage active search and health education.…”
Section: Discussionmentioning
confidence: 99%
“…HPV is another risk factor for head and neck cancer. Burlamaqui et al 25 evaluated the knowledge of university students about HPV, and only 21.1% associated it with pharyngeal cancer and 19.1% associated with larynx cancer. In this study, only 33.4% of participants made this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size calculations were based on a 90% estimated HPV knowledge prevalence for students from health sciences undergraduate courses (group 1) and 60% for students from other fields of study (group 2), with a 5% precision rate and a 95% confidence level, according to previous studies [17][18][19][20][21][22][23][24] . The formula for sample size determination (OpenEpi Epidemiologic Calculator 2006) indicated a total of 101 and 208 participants from groups 1 and 2, respectively.…”
Section: Methodsmentioning
confidence: 99%